Formulasi Dan Uji Stabilitas Sediaan Toner Ekstrak Daun Kelor (Moringa Oleifera Lam.) - Indrasari, Tika (Parapemikir : Jurnal Ilmiah Farmasi, 2025)
Skin is a very important system for the body because it can tell us about overall health. The research aims to determine whether the ethanol extract of Moringa leaves (Moringa oleifera L.) can be formulated into toner preparations and formulas that meet the stability requirements for observation for one month. This research is experimental in nature, namely by making formulations and conducting evaluation tests of the toner preparations that have been made. Evaluation test results include organoleptic, pH, homogeneity, specific gravity, viscosity and stability tests. The results of the organoleptic physical evaluation for formula 1, formula 2, and formula 3 were greenish brown, smelled of jasmine, and were in the form of a solution. Formula 1, formula 2, and formula 3 showed the same pH, namely 6. The homogeneity test results of the three formulas were less stable because precipitation occurred on day 7. The ANOVA test results showed the specific gravity value p(0.0020.05) and the viscosity value p(0.4650.05) so there is a significant effect on the specific gravity test, while there is no significant effect on the viscosity test. The conclusion obtained from this research is that Moringa leaf ethanol extract can be formulated into a toner preparation, and the three formulas have met the requirements for a 1 month physical stability test.